Safety net programs and poverty reduction : lessons from cross - country experience - Subbarao, K (Washington : The World Bank, 1997)
Conceptual issues in the analysis of social assistance and poverty - targeted programs, 15. -- Cross - country patterns of cash transfers, 25. -- Cross - country patterns of in - kind transfers, 45. -- Income generation programs, 69. -- Innovations in the delivery and organization of social assistance and poverty - targeted programs, 93. -- Moders of financing social assistance programs, 117. -- The political economy of social assistance programs, 135. -- Choosing and designing programs, 159